Cultivo do girassol irrigado sob diferentes lâminas de água e doses de nitrogênio - Freire, Jonas de Oliveira (Universidade Federal Rural do Semi-Árido, 2016)
Sunflower adapts to different conditions of climate and soil, including the prevailing climate in the Northeast, but the water needs, as well as nitrogen fertilizer recommendations are not yet fully defined. The objective of this study was to evaluate sunflower productivity and efficiency of water and nitrogen use. The experiment was conducted between October 2013 to January 2014 in Unidade Agrícola Industrial Escola do Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte (IFRN/Campus Apodi), Apodi, in the state of Rio Grande do Norte, Brazil. Statistical design used was in blocks in the 4 x 4 factorial scheme with four replications. The treatments consisted of four water slides 58, 80, 100 and 120% of crop evapotranspiration (ETc) associated with four doses of nitrogen 40, 100, 200 and 370% of the dose recommended for the cultivation of 70 kg ha-1. The depth water of 517 mm (108% ETc) associated with nitrogen dose of 77 kg ha-1 provided 91.3% of the maximum productivity, these being the doses recommended in the studied conditions. The oil productivity depending on depths water and nitrogen levels followed the trend surface function in oil yield of water depths and doses of nitrogen. The water factor was most limiting characteristics evaluated the nitrogen fertilization
Sunflower cultivation irrigated under different water blades and nitrogen doses
Keywords: Oleaginosa; Irrigação; Eficiência do Uso da Água; Eficiência no uso do nitrogênio; Line source; Oleaginous; Irrigation; Water use efficiency; Nitrogen use efficiency; Line source; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO